The big book of paw patrol ebook - Nickelodeon Publishing (PAW Patrol., 2015)
Everything you need to know about the awesome and adorable rescue pups of Nickelodeon's PAW Patrol is featured in this storybook that's sure to thrill kids ages 3 to 7. Kids will love learning all about Chase, Rocky, Marshall, Skye, Zuma, Rubble, and their tech-savvy leader—a 10-year-old boy named Ryder. This Nickelodeon Read-Along contains audio narration.